Carbon sequestration and sustainable livelihoods: a workshop synthesis - Murdiyarso, Daniel; Herawati, H.; Iskandar, H. (Center for International Forestry Research, 2005)
Carbon sequestration projects conducted as part of community development strategies can offer considerable environmental and social benefits. Such initiatives do have some degree of compatibility with the dual objectives of the Kyoto Protocols’ Clean Development Mechanism (CDM). The lessons learned from such initiatives in Mexico, Colombia, Costa Rica, Philippines, Indonesia, and Timor Leste generally demonstrate the importance of engaging strong local participation. Although most of these projects do not fully comply with the rigid guidelines governing the Kyoto Protocol’s Clean Development Mechanism, this is partly because the current agreement only allows afforestation and reforestation project activities. Conservation of areas that store large amounts of carbon, such as in peat lands, is ineligible for funding under existing rules. This synthesis also looks at how strategic approaches might be addressed for including deforestation avoidance initiatives in the next round of negotiations and subsequent commitment period. To succeed, these projects employ a scientifically sound methodology in determining the baseline, monitoring additionality and leakage, and permanence. The workshop reviewed in this paper examined a range of possibilities, including mainstreaming gender equity, reviving traditional laws and implementing adaptation measures. Findings from the workshop suggest that climate change projects must include practical livelihood options and that further investigation of donor and policy responses is needed to determine the level of public funding these projects should receive and how to best encourage private sector involvement. The complexity of these projects is demonstrated with examples from a range of on-going projects. The workshop and this synthesis provide a valuable opportunity to share the lessons learned from community-based projects in different regulatory and institutional frameworks.